Experimental investigation of pulverized coal flames in CO2/O2- and N2/O2-atmospheres: Comparison of solid particle radiative characteristics. (1st August 2017) - Zabrodiec, D.; Hees, J.; Massmeyer, A.; vom Lehn, F.; Habermehl, M.; Hatzfeld, O.; Kneer, R.
Abstract: This work presents experimental results of swirling pulverized coal flames from a 60 kW th combustion chamber based on spectrometric (UV–VIS) measurements comparing conventional air-fuel and oxy-fuel conditions. Radiation of the flames investigated was collected by two different optical systems: first, by a non-intrusive narrow-angle optical system providing integrated line-of-sight radiation data, and second, by an intrusive cold-background optical probe that collects radiation from integrated line-of-sight radiation within a reduced measurement volume. The collected spectra were processed and fitted to the Planck black body radiation function in order to estimate solid particle temperatures and relative radiant fluxes. Atomic and molecular emission lines observed are also identified and compared between the flames studied. The data obtained provide valuable insight to the different flames investigated and helpful explanations of the significant observed differences between the flames. As expected, oxidant composition was found to have a major impact on flame radiation and measured temperatures. Experimental validation data from this type of configuration and flame conditions are scarce, thus, the data may serve as validation data for numerical models.